Dividend Policy of Russian Companies with State Participation as a Mechanism of Relations with the Owners - Reshetnikova, Tatyana V.; Reshetnikov, Alexey I.; Tatiannikov, Vasilii A. (Amazonia Investiga, 2020)
The formation and implementation of the dividend policy of Russian companies with state participation differ from the policies pursued by the public and non-public joint-stock companies owned by private investors. The state, being a special shareholder, affects the dividend policy from the position of the owner and the regulator, who has the ability to set certain restrictions and rules for companies that are not in the power of other categories of shareholders. Systemic risks and the uncertainty of the development of the Russian economy objectively require an in-depth study of the regulation of dividend policy in public companies with state participation. It is generally accepted that with a decrease in the number of dividends paid to owners of ordinary shares, the weighted average cost of capital becomes lower, while at the same time the financial performance of a business and the amount of retained earnings become higher. Therefore, the company's dividend policy is an important element of financial management and relations with the owners. The question of the importance of dividend policy for public companies with state participation is the most controversial and little studied today. The price of shares, the structure of equity capital, and the need to attract borrowed capital are directly dependent on the size of dividends. However, the payment of dividends reduces the amount of profit that can be reinvested in the development of the company, so the impact of dividend policy on the financial condition of the company is ambiguous. In this regard, it seems relevant to improve the dividend policy of public companies with state participation through solving the problems existing in them.